Postural stability at activation and deactivation of the cochlear implant in adolescents with late lateral implantations: a quasi-experiment - Anna Zwierzchowska; Eliza Gaweł; Agata Krużyńska; Kajetan J. Słomka; Grzegorz Juras (BMC, 2024)
Abstract Background Cochlear implantation (CI) surgery has become a prevalent method of hearing rehabilitation, since it has been acknowledged that it impacts effectively on the vestibular system. However, there is still no consensus among clinicians on the most appropriate age and area (lateral/bilateral) of CI surgery in terms of postural control. The present study aimed to assess the postural control in late lateral CI adolescents with different visual (eyes opened(EO)/eyes closed(EC)) and auditory (CI activated/deactivated) conditions and to build a theoretical model of postural control based on sensual compensatory mechanisms that are predominant in late CI individuals. It was hypothesized that kinesthetic sensation and exteroceptors of the superficial sensation are critical for neuromuscular control after late CI. Methods A quasi-experimental study protocol was used in this study to assess the postural stability performance in the studied adolescents with different visual and auditory perceptions. 27 adolescent students with hearing loss participated in the study. A force plate (Accu Gait AMTI) with computer software (NetForce) was used in the study to assess the postural stability with four different conditions(EO)/EC), CI activated/deactivated). Results vCOP was found to have a significant growing tendency within the conditions of CI activated/deactivated.No statistically significant relationships were noted between the range of the displacement of feet pressure (Area) and both the visual and auditory conditions. Hearing loss etiology was statistically significantly related to the values of vCOP, within the conditions of EO, CI activated/deactivated (p < 0.01), what did not occure with the condition of EC (p > 0.05). Neuromuscular control with the condition of EC x CI deactivated was found to be based on the kinesthetic-tactual compensatory model. Conclusions Kinesthetic sensation and exteroceptors of the superficial sensation seem to be the predominant source of information to maintain postural control in late CI adolescents, regardless of the visual and auditory conditions. The etiology of hearing loss (congenital/acquired) can be a predictor of the values of the vCOP. In order to improve neuromuscular control in this population, it is recommended that the patients perform physical activity tasks, especially to develop core muscles, based on direct stimulation and rotational stability.